Fibroblast heterogeneity in pancreatic ductal adenocarcinoma: Perspectives in immunotherapy. (December 2022) - Luong, Tha; Golivi, Yuvasri; Nagaraju, Ganji Purnachandra; El-Rayes, Bassel F.
Abstract: Cancer-associated fibroblasts (CAFs), the key component in pancreatic tumor microenvironment (TME), originate from many sources and are naturally heterogeneous in phenotype and function. Numerous studies have identified their crucial role in promoting tumorigenesis through many routes including fostering cancer proliferation, angiogenesis, invasion, and metastasis. Conversely, research also indicates that subsets of CAFs express anti-tumor activity. These dual effects reflect the complexity of CAF heterogeneity and their interactions with other cells and factors in pancreatic TME. A critical component in this environment is infiltrated immune cells and immune mediators, which can communicate with CAFs. The crosstalk occurs via the production of various cytokines, chemokines, and other mediators and shapes the immunological state in TME. Comprehensive studies of the crosstalk between CAFs and tumor immune environment, particularly internal mechanisms interlinking CAFs and immune effectors, may provide new approaches for pancreatic ductal adenocarcinoma (PDAC) treatments. In this review, we explore the characteristics of CAFs, describe the interplay among CAFs, infiltrated immune cells, other mediators, and provide an overview of recent CAF-target therapies, their limitations, and potential research directions in CAF in the context of PDAC. Graphical Abstract: ga1 Highlights: Reviewed cancer-associated fibroblasts (CAFs) in tumor microenvironment (TME) of pancreatic ductal adenocarcinoma (PDAC). Explored various origins, phenotypes, and diverse functions of CAFs, which play a crucial role in PDAC progression. Studied CAFs and TME (immune cells, and their mediators) interactions on PDAC growth. Discussed the development of CAF-targeted therapies, future directions, and challenges.